THE NAHDLIYAH SPIRITUAL VALUE PERSPECTIVE IN ANALYZING THE ROLE OF FINANCIAL PERFORMANCE OF MSME - Santoso, Bedjo; Hendar, Hendar; Zaenudin, Zaenudin; Haron, Razali Bin (Jurnal Aplikasi Manajemen, 2023)
The most researches related to the Nahdlatul Ulama (NU) community business performance is just focus on the role of entrepreneur, ICT, e-commerce, marketing, and other common variables that have ignored the important concept which initiated from the main value of the NU's movement philosophy. It is therefore, this study aimed to analyses the role of Nahdliyah spiritual value (NSV) to NU's business performance. NSV considered as new concept synthesized by combining resource advantage on competition theory (RACT) and social identity theory (SIT) inserted by Nahdliyin value concept. The object of this research is the NU business community members of the NU Entrepreneurs Association (HPN). This study used a quantitative method with purposive sampling to select 350 MSMEs (UMKM) under HPN in Central Java and tested the regressive relationship of 6 variables with SEM PLS 4.0. The findings show that digital marketing capabilities, ICT, and entrepreneurial spirit are the factors that most support the existence of NSV. Besides that, NSV plays a role in mediating the relationship between these three factors to financial performance in an MSME. This study fulfils the theoretical gaps and produces new perspectives into the spiritual value concept of resource advantage theory on the competition by inserting spiritual values implemented in MSMEs based on spiritual community businesses. This research contributes to the development of a new concept of NSV. The study also covered the research gap related to the relationship between the variables involved.